A sequence is given by the recursive formula
`a_1=10, \ a_(n+1)=3a_n+4` for `n>=1`
Using mathematical induction to show the formula for the general term of the sequence is
`a_n=4(3^n)-2` (3 marks)
--- 8 WORK AREA LINES (style=lined) ---
Aussie Maths & Science Teachers: Save your time with SmarterEd
A sequence is given by the recursive formula
`a_1=10, \ a_(n+1)=3a_n+4` for `n>=1`
Using mathematical induction to show the formula for the general term of the sequence is
`a_n=4(3^n)-2` (3 marks)
--- 8 WORK AREA LINES (style=lined) ---
`text{Proof (See Worked Solution)}`
`text{Prove true for}\ \ n=1:`
`text{LHS}\ =a_1=10`
`text{RHS}\ =4(3^1)-2=10=\ text{LHS}`
`:.\ text{True for}\ \ n=1`
`text{Assume true for}\ \ n=k:`
`a_k=4(3^k)-2\ \ text{… (1)}`
`text{Prove true for}\ \ n=k+1:`
`text{i.e.}\ a_(k+1)=4(3^(k+1))-2`
`a_(k+1)` | `=3a_k+4` | |
`=3[4(3^k)-2]+4` | ||
`=4*3^k*3-6+4` | ||
`=4(3^(k+1))-2` | ||
`=\ text{RHS}` |
`:.\ text{True for}\ \ n=k+1`
`:.\ text{Since true for} \ n=1,\ text{by PMI, true for integers} \ n>=1.`
Let `J_(n)=int_(0)^(1)x^(n)e^(-x)\ dx`, where "n" is a non-negative integer.
--- 2 WORK AREA LINES (style=lined) ---
--- 3 WORK AREA LINES (style=lined) ---
--- 4 WORK AREA LINES (style=lined) ---
--- 6 WORK AREA LINES (style=lined) ---
--- 5 WORK AREA LINES (style=lined) ---
i. | `J_0` | `=int_0^1 e^(-x)\ dx` |
`=[-e^(-x)]_0^1` | ||
`=-e^(-1)+1` | ||
`=1-1/e` |
ii. `text{Show}\ \ J_n<=1/(n+1)`
`text{Note:}\ e^(-x)<1\ \ text{for}\ \ x in [0,1]`
`J_n` | `=int_0^1 x^n e^(-x)\ dx` | |
`leq int_0^1 x^n \ dx` | ||
`leq 1/(n+1)[x^(n+1)]_0^1` | ||
`leq 1/(n+1)(1^(n+1)-0)` | ||
`leq 1/(n+1)\ \ text{… as required}` |
iii. `text{Show}\ \ J_n=nJ_(n-1)-1/e`
`u` | `=x^n` | `v′` | `=e^(-x)` |
`u′` | `=nx^(n-1)` | `v` | `=-e^(-x)` |
`J_n` | `=[-x^n * e^(-x)]_0^1-int_0^1 nx^(n-1)*-e^(-x)\ dx` | |
`=(-1^n * e^(-1)+0^n e^0)+nint_0^1 x^(n-1)*e^(-x)\ dx` | ||
`=nJ_(n-1)-1/e` |
iv. `text{Prove}\ \ J_(n)=n!-(n!)/(e)sum_(r=0)^(n)(1)/(r!)\ \ text{for}\ \ n >= 0`
`text{If}\ \ n=0:`
`text{LHS} = 1-1/e\ \ text{(see part (i))}`
`text{RHS} = 0!-0!/e (1/(0!)) = 1-1/e(1)=\ text{LHS}`
`:.\ text{True for}\ \ n=0.`
`text{Assume true for}\ \ n=k:`
`J_(k)=k!-(k!)/(e)sum_(r=0)^(k)(1)/(r!)`
`text{Prove true for}\ \ n=k+1:`
`text{i.e.}\ \ J_(k+1)=(k+1)!-((k+1!))/(e)sum_(r=0)^(k+1)(1)/(r!)`
`J_(k+1)` | `=(k+1)J_k-1/e\ \ text{(using part (iii))}` | |
`=(k+1)(k!-(k!)/(e)sum_(r=0)^(k)(1)/(r!))-1/e` | ||
`=(k+1)!-((k+1)!)/(e)sum_(r=0)^(k)(1)/(r!)-1/e xx ((k+1)!)/((k+1)!)` | ||
`=(k+1)!-((k+1)!)/e(\ sum_(\ r=0)^(k)(1)/(r!)+1/((k+1)!))` | ||
`=(k+1)!-((k+1)!)/e(\ sum_(\ r=0)^(k+1)(1)/(r!))` |
`=>\ text{True for}\ \ n=k+1`
`:.\ text{S}text{ince true for}\ n=1,\ text{by PMI, true for integers}\ n>=1`
v. `0<=J_n<= 1/(n+1)\ \ \ text{(part (ii))}`
`lim_(n->oo) 1/(n+1)=0\ \ => \ lim_(n->oo) J_n=0`
`text{Using part (iv):}`
`J_n/(n!)` | `=1-1/e sum_(r=0)^(n)(1)/(r!)` | |
`1/e sum_(r=0)^(n)(1)/(r!)` | `=1-J_n/(n!)` | |
`sum_(r=0)^(n)(1)/(r!)` | `=e-(eJ_n)/(n!)` | |
`lim_(n->oo)(\ sum_(\ r=0)^(n)(1)/(r!))` | `=lim_(n->oo)(e-(eJ_n)/(n!))` | |
`=e-0` | ||
`=e` |
The numbers `a_(n)`, for integers `n >= 1`, are defined as
`{:[a_(1)=sqrt2],[a_(2)=sqrt(2+sqrt2)],[a_(3)=sqrt(2+sqrt(2+sqrt2)) \ text{, and so on.}]:}`
These numbers satisfy the relation `a_(n+1)^(2)=2+a_(n)`, for `n >= 1`. (Do NOT prove this)
Use mathematical induction to prove that `a_(n)=2cos\ pi/(2^(n+1))`, for all integers `n >= 1`. (4 marks)
`text{Proof (See Worked Solution)}`
`text{Prove}\ \ a_(n)=2cos(pi/(2^(n+1)))\ \ text{for}\ \ n >= 1`
`text{If}\ \ n=1:`
`a_1=2cos((pi)/(2^2))=2xx1/sqrt2=sqrt2`
`:.\ text{True for}\ n=1.`
`text{Assume true for}\ \ n=k:`
`a_(k)= =2cos(pi/(2^(k+1)))`
`text{Prove true for}\ \ n=k+1:`
`text{i.e.}\ \ a_(k+1)= 2cos(pi/(2^(k+2)))`
`text{LHS}` | `=sqrt(2+a_k)` | |
`=sqrt(2+2cos(pi/(2^(k+1)))` | ||
`=sqrt(2+2 cos(2 xx (pi/(2^(k+2)))))\ \ \ text{(using}\ \ cos(2theta)=2cos^2theta-1text{)}` | ||
`=sqrt(2+2(2cos^2(pi/(2^(k+2)))-1)` | ||
`=sqrt(2+4cos^2(pi/(2^(k+2)))-2)` | ||
`=sqrt(4cos^2(pi/(2^(k+2)))` | ||
`=2cos(pi/(2^(k+2)))` | ||
`=\ text{RHS}` |
The sequence `{x_n}` is given by
`x_1 = 1` and `x_(n + 1) = (4 + x_n)/(1 + x_n)` for `n >= 1.`
--- 10 WORK AREA LINES (style=lined) ---
--- 2 WORK AREA LINES (style=lined) ---
i. `text(If)\ \ n = 1`
`x_1=2 ((1 – 1/3)/(1 + 1/3))=(2 xx 2/3)/(4/3)=1`
`:.text(True for)\ \ n = 1`
`text(Assume true for)\ \ n=k,`
`text(i.e.)\ \ \ \ x_k = 2 ((1 + alpha^k)/(1 – alpha^k))`
`text(Prove true for)\ \ n=k+1`
`text(i.e.)\ \ \ \ x_(k + 1) = 2 ((1 + alpha^(k + 1))/(1 – alpha^(k+1)))`
`x_(k + 1) =` | `(4 + x_k)/(1 + x_k)` |
`=` | `(4 + 2 ((1 + alpha^k)/(1 – alpha^k)))/(1 + 2((1 + alpha^k)/(1 – alpha^k)))` |
`=` | `2 [(2(1 – alpha^k) + (1 + alpha^k))/(1 – alpha^k + 2 (1 + alpha^k))]` |
`=` | `2 [(2 – 2 alpha^k + 1 + alpha^k)/(1 – alpha^k + 2 + 2 alpha^k)]` |
`=` | `2 [(3 – alpha^k)/(3 + alpha^k)]` |
`=` | `2 [(1 – alpha^k xx 1/3)/(1 + alpha^k xx 1/3)]` |
`=` | `2 [(1 + alpha^k xx alpha)/(1 – alpha^k xx alpha)],\ \ \ \ (alpha=-1/3)` |
`=` | `2 [(1 + alpha^(k + 1))/(1 – alpha^(k + 1))]` |
`=` | `text(RHS)` |
`:.text(True for)\ \ n = k + 1\ \ text(if it is true for)\ \ n = k.`
`:.text(S)text(ince true for)\ \ n=1, text(by PMI, true for all integral)\ \ n >= 1.`
ii. `text(S)text(ince)\ \ lim_(n -> oo) (-1/3)^n=0`
`:.lim_(n -> oo) x_n` | `=2 ((1 + (-1/3)^n)/(1 – (-1/3)^n))` |
`=2` |
A sequence `a_n` is defined by
`a_n = 2a_(n − 1) + a_(n − 2)`,
for `n ≥ 2`, with `a_0 = a_1 = 2`.
Use mathematical induction to prove that
`a_n = (1 + sqrt2)^n + (1 − sqrt2)^n` for all `n ≥ 0`. (3 marks)
--- 10 WORK AREA LINES (style=lined) ---
`text{Proof (See Worked Solutions)}`
`text(Prove)\ \ a_n = (1 + sqrt2)^n + (1 − sqrt2)^n\ text(for all)\ n ≥ 0.`
`text(where)\ a_0 = a_1 = 2, and \ a_n = 2a_(n − 1) + a_(n − 2)\ \ text(for)\ \ n ≥ 2,\ `
`text(When)\ \ n=0,` | `a_0` | `= (1 + sqrt2)^0 + (1 − sqrt2)^0` |
`= 1 + 1=2` | ||
`text(When)\ \ n=1,` | `a_1` | `= (1 + sqrt2)^1 + (1 − sqrt2)^1` |
`= 1 + sqrt2 + 1 − sqrt2=2` |
`:.\ text(True for)\ n=0\ \ and\ n=1`
`text(Assume that)`
`a_k = (1 + sqrt2)^k + (1 − sqrt2)^k\ text(and)`
`a_(k − 1) = (1 + sqrt2)^(k − 1) + (1 − sqrt2)^(k − 1)\ text(for all)\ k ≥ 1.`
`text(Prove true for)\ \ n = k + 1`
`text(i.e.)\ \ a_(k + 1) = (1 + sqrt2)^(k + 1) + (1 − sqrt2)^(k + 1).`
`a_(k + 1)` | `= 2a_k + a_(k − 1).` |
`= 2(1 + sqrt2)^k + 2(1 − sqrt2)^k + (1 + sqrt2)^(k − 1) + (1 − sqrt2)^(k − 1)` | |
`= (1 + sqrt2)^(k − 1)(2 + 2sqrt2 + 1) + (1 − sqrt2)^(k − 1)(2 − 2sqrt2 + 1)` | |
`= (1 + sqrt2)^(k − 1)(1 + sqrt2)^2 + (1 − sqrt2)^(k − 1)(1− sqrt2)^2` | |
`= (1 + sqrt2)^(k + 1) + (1 − sqrt2)^(k + 1)` |
`=>\ text(True for)\ \ n = k + 1\ \ text(if it is true for)\ \ n = k\ \ text(and)\ \ n = k − 1.`
`:.\ text(S)text(ince true for)\ n = 0 and n=1,\ text(by PMI, it is)`
`text(true for integral)\ n ≥ 0.`